2020
DOI: 10.26434/chemrxiv.13049531.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of Nanostructure Development from the Molecular Dynamics of Poly(pentamethylene 2,5- Furanoate)

Abstract: <div><div><div><p>We report on the molecular origin of poly(pentamethylene 2,5-furanoate) particular physical properties. From the structural point of view we found this polymer can develop crystallinity when stored at room conditions for months. On the other hand, we used broadband dielectric spectroscopy (BDS) measurements, to analyze in very detail the local and segmental molecular dynamics of the material subjected to several thermal treatments. In this way we evidenced that the mol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…Besides, the structural development seems to be completed nearly after 6 months, presenting the 6 months-and 1 year-aged films practically the same features. The slow crystallization kinetics in the PPeF thin films are in line with bulk calorimetric studies on this polymer [40]. In fact, in the present case we observed nanostructures resembling those of the non-symmetrical spherulites typically developed by polymers at low undercooling degree.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Besides, the structural development seems to be completed nearly after 6 months, presenting the 6 months-and 1 year-aged films practically the same features. The slow crystallization kinetics in the PPeF thin films are in line with bulk calorimetric studies on this polymer [40]. In fact, in the present case we observed nanostructures resembling those of the non-symmetrical spherulites typically developed by polymers at low undercooling degree.…”
Section: Resultssupporting
confidence: 91%
“…Then, the PPeF thin film presented a high mechanical stability even though in the rubbery state and in a confined geometry. This finding is in line with the interesting bulk properties of furanbased polymers, particularly those observed for PPeF in recent works [9,11,40]. In fact, Martínez-Tong and collaborators showed that this polymer does not reach Newtonian flow at high temperatures (120 -150 ºC), as observed by rheology measurements [40].…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations